Effects of cognitive learning styles on the academic achievement of secondary school adolescents: implications for counselling (2009)
"The purpose of this study was to investigate the effects of cognitive learning styles on the academic achievement of adolescent in secondary schools in Ibadan. Descriptive survey research design was employed. A total of 500 (male 267; female 233) adolescent students randomly selected from ten secondary schools were involved in the study. Their age ranged between 12 and 15 with mean age of 13.5 years. The academic records of the students were obtained from their principals. Student t-test statistic and Pearson's product moment correlation was used to analyse the data collected. Results indicated that there was a significant influence of gender on the academic achievement of male and female students; also a significant relationship was found between the cognitive learning styles and academic achievement of the students. The implications of the findings from this study are that educational and counselling psychologists could use cognitive learning styles as variables to predict the academic achievement of the students. Teachers should also provide active learning opportunities rather than chalk and talk, provide immediate feedback and emphasize mastery over performance goals. "